Heterogeneity of propyl-ammonium nitrate solid phases obtained under high pressure. (September 2015) - Capitani, Francesco; Fasolato, Claudia; Mangialardo, Sara; Signorelli, Sara; Gontrani, Lorenzo; Postorino, Paolo
Abstract: A recent work reported on different solid phases obtained on the protic ionic liquid propyl-ammonium nitrate (PAN) under a pressure up to 2 GPa. However, the experimental parameters and measurement protocols driving the solidification process were not clarified. Here, we report on and discuss three different Raman measurements on PAN carried out over different pressure ranges (up to 4 GPa). Exploiting different pressure increasing rates for each measurement we obtained a variety of solid phases. The differences between these phases are highlighted by visual inspection, by different solidification pressure values and by the Raman spectroscopic features relative to the anion stretching mode and to the cation alkyl chain vibration. Our results indicate different local structures surrounding the ionic couple in the solid phase and the capability of pressure to lock the cation alkyl chain in conformations different from those of the liquid state. These evidences also suggest the use of systematic and careful measurement protocols in order to reproduce a particular solid phase of PAN under pressure. Abstract : Highlights: PAN shows a rich polymorphism under pressure. Different pressure increasing rates lead to different liquid–solid transition pressures. Solid phase presents a distorted H-bonding network around anions. Cation conformers in the solid phase differ from those of the liquid state.